The location and extent of exfoliation of clay on the fracture mechanisms in nylon 66-based ternary nanocomposites - Dasari, Aravind (2014)
The primary focus of this work is to elucidate the location and extent of exfoliation of clay on fracture (under both static and dynamic loading conditions) of melt-compounded nylon 66/clay/SEBS-g-MA ternary nanocomposites fabricated by different blending sequences. Distinct microstructures are obtained depending on the blending protocol employed. The state of exfoliation and dispersion of clay in nylon 66 matrix and SEBS-g-MA phase are quantified and the presence of clay in rubber is shown to have a negative effect on the toughness of the nanocomposites. The level of toughness enhancement of ternary nanocomposites depends on the blending protocol and the capability of different fillers to activate the plastic deformation mechanisms in the matrix. These mechanisms include: cavitation of SEBS-g-MA phase, stretching of voided matrix material, interfacial debonding of SEBS-g-MA particles, debonding of intercalated clay embedded inside the SEBS-g-MA phase, and delamination of intercalated clay platelets. Based on these results, new insights and approaches for the processing of better toughened polymer ternary nanocomposites are discussed.